LncRNA UCA1 regulates immune micro-environment in cisplatin-induced AKI by miRNA-4498/AKT3 pathway. - Peng Hongjun; Lydia Mukanhaire; Liu Zhen; Wang Ting; Li Hongye; Zhang Xiaotian; Liu Guangling; Ren Xianguo (PLoS ONE)
An increasing number of studies highlight the significance of long non-coding RNAs (lncRNAs) in the biological process of acute kidney injury (AKI). This study investigates the role and the mechanism of lncRNA UCA1 in cisplatin-induced AKI. Real-time quantitative PCR was used to measure lncRNA UCA1 expression in cisplatin-induced AKI mouse model, showing that lncRNA UCA1 was overexpressed. Knockdown of lncRNA UCA1 by shRNA significantly reduced inflammation caused by cisplatin treatment. A co-culture system demonstrated that lncRNA UCA1 upregulation in T cells induced apoptosis of tubular epithelial cells (TECs). A dual-luciferase reporter assay confirmed that lncRNA UCA1 acts as a miR-4498 sponge, binding to the 3'UTR of AKT3. Flow cytometry and ELISA results showed that reduced inflammation effect induced by lncRNA UCA1 knockdown was reversed by miR-4498 inhibition or AKT3 overexpression. Our findings suggest that lncRNA UCA1 functions as a miR-4498 sponge, upregulating AKT3 expression, and promoting inflammation in cisplatin-induced AKI.